2004
DOI: 10.1159/000077122
|View full text |Cite
|
Sign up to set email alerts
|

Role of Urinary Zinc and Copper on Calcium Oxalate Stone Formation

Abstract: Introduction: It is considered that many factors may play a role in urolithiasis. Experimental and clinical studies have shown that zinc has an inhibitory effect on urolithiasis. Materials and Methods: In this study, urinary zinc and copper were measured in 27 healthy controls and 30 calcium oxalate stone formers. Results: Urinary zinc excretion was significantly higher (p < 0.001) in stone formers than healthy controls (2,575 ± 274 and 960 ± 80 mg/day, respectively). There was no significant difference in uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 11 publications
3
20
1
Order By: Relevance
“…However the others, found significantly higher amounts of Cu in urinary excretion of stone patients [1,6,7]. Some studies showed that serum levels of Cu do not show any difference between stone patients and heathy controls [3,7,8]. In the present study, the mean urinary Cu levels in stone patients was 0.16 ± 0.5 ppm and was significantly higher than healthy controls.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…However the others, found significantly higher amounts of Cu in urinary excretion of stone patients [1,6,7]. Some studies showed that serum levels of Cu do not show any difference between stone patients and heathy controls [3,7,8]. In the present study, the mean urinary Cu levels in stone patients was 0.16 ± 0.5 ppm and was significantly higher than healthy controls.…”
Section: Discussioncontrasting
confidence: 53%
“…Meyer and Angino [5] observed the inhibitory effect of Cu on calcium phosphate stones but they also reported that Cu did not affect the crystal growth of calcium oxalate. Some authors detected no differences relating to Cu urinary excretion between stone patients and healthy controls [3,8,13,14]. However the others, found significantly higher amounts of Cu in urinary excretion of stone patients [1,6,7].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We made the hypothesis these groups of proteins are more important in the process of crystal formation based on previous published work. [20][21][22][23] We have previously looked into a different cohort of flies for the corresponding transcriptive changes (data not shown), but the candidate proteins cannot be correlated at the mRNA level.…”
Section: Discussionmentioning
confidence: 99%